Bioavailability of Iron in Chicken Nuggets with the Addition of Chicken Liver and Moringa Leaves - Sofyan Musyabiq Wijaya; Sri Anna Marliyati; Dodik Briawan; Eny Palupi (Media Publikasi Cendekia Indonesia, 2026)
Anemia is a global health problem caused by iron deficiency, especially among vulnerable groups such as adolescents. One of the strategies to prevent anemia is through the consumption of foods rich in iron and other supporting nutrients. Chicken nuggets are a popular processed meat product with the potential to develop into a functional food. This can be achieved by fortifying them with iron-rich ingredients, such as chicken liver and moringa leaves. This research aims to determine the bioavailability of iron in chicken nugget products containing chicken liver and moringa leaves. The production of chicken nuggets with the addition of chicken liver and moringa leaves was divided into two treatments: Control (100% chicken meat) and P (75% chicken meat: 20% chicken liver: 5% moringa leaves). The P formula was selected based on previously conducted sensory tests. Nutritional content test using the proximate test. Iron bioavailability analysis using pepsin and pancreatin enzymes with 4 repetitions. Results were analyzed using an Independent-Samples T-Test. There were significant differences for energy content (p = 0.014), carbohydrate percentage (p = 0.031), and protein percentage (p = 0.001), and no significant differences for fat percentage (p = 0.207). There was no significant difference for iron content (p = 0.184), but there was a significant difference for iron absorbed (p = 0.013) and percentage of iron bioavailability (p = 0.034). The addition of chicken liver and moringa leaves was found to significantly increase the bioavailability of iron in the product